DEVELOPMENT OF A BOARDING HOUSE INFORMATION SYSTEM WITH 360° VIRTUAL TOUR - Aulia Aziiza, Arizia; Darrel, Rafael; Prijambodo, Bambang (Institut Teknologi Nasional Malang, 2025)
An information system in the boarding house business is needed to manage the entire booking process from receipt, verification the availability, and payment process. Based on questionnaires and interviews, there is a problem with the conventional boarding house booking process, which needs to be more efficient. The boarding house owner tracks room availability in a notebook. When a boarder wants to rent, the manager checks the notebook, which is time-consuming and only provides general information without visual details of the rooms. Meanwhile, prospective boarders often seek information about the room's condition and choose to conduct surveys to assess the boarding house before renting. This study aims to simplify the process for prospective boarders, who often survey boarding houses to check room conditions, by creating an information system with detailed room info, a 360° virtual tour, online booking, and payment features. This research was conducted by following the stages of the Software Development Lifecycle (SDLC) using the waterfall model. Verification was performed through program trials by the boarding house owner and boarders, followed by interviews to obtain validation from relevant parties. The results indicate that the system functions effectively and streamlines administration, booking, and online maintenance reporting in boarding house.